307 The Importance of Traditional Education in Medical Laboratory Science. (11th January 2018) - Lawson, Shane; Ledesma, Carlo
Abstract: As the practice of medical laboratory science has experienced a significant amount of shortage of qualified personnel, medical laboratory leadership have resorted to Clinical Laboratory Improvement Amendments (CLIA)-qualified, non-traditionally educated testing personnel, and as a result, the field of medical laboratory science has become inundated with inexperienced technologists. It is paramount to ensure that medical laboratories hire the most qualified individuals to fill vacant positions. Oftentimes, laboratories cut corners to fill positions with underqualified employees when staffing reaches critical levels. This study seeks to build on the hypothesis that traditionally educated laboratory scientists fill these positions more adequately than those who have been non-traditionally educated. If these positions are filled with personnel who do not have a solid foundation in laboratory medicine, the patients served by the laboratory are more likely to fall victim to slower turnaround times and inaccurate test results. In this study, anonymous surveys in electronic format were submitted to lab directors, managers, and supervisors who are involved in the selection and hiring of laboratory testing personnel; the survey asked opinion-based questions about employees who have received traditional MLS or MLT college educations vs those who received their bachelor's degrees in a life science and later went on to work in the lab. Of the respondents, 82% stated that they were understaffed, if not critically understaffed, with laboratory testing personnel. Of the same respondents, 65% employed "non-traditional" technologists, and approximately 82% of the laboratories require ASCP or AMT certification. Of the respondents, 79% received a degree through an MLS or MLT program, and the other 21% were considered "non-traditional" laboratorians. Approximately 70% of the laboratories do not provide extra training time for non-traditionally educated personnel, which impacts the quality of testing. Of the laboratories that employ non-traditional technicians, 67% attributed technical errors to the non-traditional personnel, and only 33% to traditionally educated scientists. The overwhelming response to the survey was that the vast majority of those in laboratory leadership stated that filling positions with non-traditional laboratorians, despite their qualifications as testing personnel, has resulted in more technical errors in their laboratories. Non-traditional laboratory testing roles are filled perhaps through laboratory specimen processors that possess educational requirements that qualify them as testing personnel according to CLIA. It is a result of this survey that traditionally educated laboratory personnel, ie, graduates of MLS/MLT programs, have fewer quality issues compared to their counterparts. The more errors that happen in the medical laboratory, the more adversely affected our patients are. Even during an employment drought, quality in the practice of laboratory medicine needs to be of the utmost importance. Cutting corners to fill technical positions has not proven to be a beneficial business practice. This survey reflects the practice in Oklahoma; the group recommends further studies be done to reflect a regional or national trend.